Diverse Role of Silicon Carbide in the Domain of Nanomaterials - T. Sahu; B. Ghosh; S. K. Pradhan; T. Ganguly (International Journal of Electrochemistry)
Silicon carbide (SiC) is a promising material due to its unique property to adopt different crystalline polytypes which monitor the band gap and the electronic and optical properties. Despite being an indirect band gap semiconductor, SiC is used in several high-performance electronic and optical devices. SiC has been long recognized as one of the best biocompatible materials, especially in cardiovascular and blood-contacting implants and biomedical devices. In this paper, diverse role of SiC in its nanostructured form has been discussed. It is felt that further experimental and theoretical work would help to better understanding of the various properties of these nanostructures in order to realize their full potentials.